Polycyclic Aromatic Hydrocarbons in Road Dust in Changchun City, Northeast China: Spatial Distribution, Source Appointment, and Human Health Risk Assessment - Na Li; Qingqing Li; Fuchen Zhu; Peng Liu; Zhaowei Wang; Zhao Chen; Weizheng Han; Kaize Wang; Keyi Hou; Yanxue Xu (Advances in Meteorology)
This study thoroughly examined the impact of coal burning on the emission of polycyclic aromatic hydrocarbons (PAHs) and their subsequent long-lasting presence in different environmental matrices, including road dust. The aim was to identify the origin, extent, spatial arrangement, and cancer-causing potential associated with PAHs in road dust in Changchun City, Northeast China. The levels of Σ16 PAHs in the road dust samples ranged from 0.314 to 17.418 mg/kg, with an average concentration of 1.4452 mg/kg, exhibiting lower values than cities worldwide. In Changchun City, PAH levels in various regions follow the order of Chaoyang (CY) > Lvyuan (LY) > Kuancheng (KC) > Jingyue (JY) > Nanguan (NG) > Er’dao (ErD). Road dust primarily comprised PAHs containing 4–5 rings among these substances. The incremental lifetime cancer risk (ILCR) analysis indicated that adults faced potential risk (>10−6) at 97.7% of the sampling sites, while children faced potential risk (>10−6) at 48.8%. The principal component analysis (PCA) model identified five potential origins of PAHs, including petroleum (22.2%), coal burning (19.1%), biomass burning (30.5%), fossil fuel burning (15.8%), and transportation (12.4%). Further investigations are required to scientifically and systematically determine the carcinogenic risks associated with PAHs in the total environment, despite estimating only potential risks from PAHs in road dust and human exposure to various environmental matrices.